Equine spermatozoa at optimum physiological state are selected by chemotaxis toward progesterone - Dominguez, Esteban Mauricio (2018)
The success of assisted reproduction techniques depends inpart on sperm quality, which influences not only fertilization butalso embryo development and implantation. In our laboratory, wedesigned the Sperm Selection Assay (SSA) based on chemotaxistowards progesterone, which selects human sperm at optimumphysiological state (capacitated, with low levels of DNA fragmentation and reactive oxygen species). The aim of this study was todefine the experimental conditions to apply the SSA in unsexedand sexed equine sperm samples. Cryopreserved sperm samples ofthree stallions were conventionally thawed, removing the seminalplasma and cryoprotectant by a modified swim up procedure.Spermatozoa were incubated in BWW media with or without capacitating conditions (25 mM NaHCO3 and 0.3% BSA), at 38.5C atan atmosphere of 5% CO2 on air, for 45 minutes. The SSA deviceconsists of two wells connected by a tube. Well 1 (W1) was filledwith the sperm suspension and well 2 (W2) with the attractantsolution, which diffused along the connecting tube as a gradient.The percentage of sperm accumulation in W2 was determined asthe difference between with and without attractant. Firstly, weestablished the capacitation conditions in equine sperm samplesby inducing the the acrosome reaction (AR) with A23187 calciumionophore, and by the protein tyrosine phosphorylation pattern(PY). The level of capacitated spermatozoa was significantlyincreased at 45 minutes of incubation vs non-capacitated control. Next, we defined the experimental conditions to set up theSSA with frozen-thawed, unsexed and sexed equine spermatozoa, determining the percentage of accumulated spermatozoa inW2 under several dose response conditions and timing: byplacing 2 million sperm per ml in W1 (162% and 192%,respectively), 10 pM progesterone in W2 as the attractant solution (132% and 172%, respectively), and running the SSA for10 min (92% and 182%, respectively). We next verifiedwhether the sperm selection in the SSA was indeed mediated bychemotaxis. Thus, sperm accumulation in W2 was only observedwhen capacitated spermatozoa were loaded in W1 and progesterone was displayed as an ascending gradient (102%). Thequality of selected spermatozoa in W2 containing progesteronewas better than that of spermatozoa without being selected bythe SSA where a significant higher level of capacitated spermatozoa (PY) and lower level of DNA fragmentation (evaluated bythe ?Halo sperm test?), for sexed and unsexed samples, wereobserved. In conclusion, equine spermatozoa are selected bychemotaxis towards progesterone are at the optimum functionalstate, at a similar extent in sexed and unsexed samples. Theresults have potential application to improve current equinereproductive biotechnologies